Unveiling the Role of Protean Career Orientation and Leadership in Organizational Commitment and Employee Performance: A Systematic Literature Review - Asmini, Asmini; Yusuf, Andi Muhammad (Universitas Muhammadiyah Ponorogo, 2025)
In today’s dynamic organizational environment, Protean Career Orientation (PCO) and leadership are critical drivers of organizational commitment and employee performance. While extensively studied separately, their combined effects remain underexplored. This study systematically reviews empirical research to clarify how PCO and leadership interact to influence employee outcomes. A systematic literature review was conducted using Scopus-indexed articles published between 2014 and 2024. Targeted keywords related to performance management, leadership, and PCO guided the search. Applying PRISMA protocol and strict inclusion criteria, 863 high-quality studies were retained for qualitative synthesis. PCO was found to positively influence affective and normative commitment through organizational identification, career optimism, and mentoring, but had limited effect on continuance commitment. Leadership styles—particularly participative, transformational, and managerial coaching—consistently improved commitment and performance. The synergy between PCO and supportive leadership promoted proactive behaviors and organizational citizenship, mediating performance gains. The findings emphasize the need for organizations to integrate career autonomy with empowering leadership to strengthen commitment and enhance performance. The proposed framework advances theory by linking PCO with leadership-driven engagement. Practically, it offers HR strategies for fostering autonomy, development, and supportive leadership. Limitations include reliance on secondary data and lack of industry-specific focus.